The grammatical forms of expressions to persons in contemporary Ukrainian political discourse: standard and practice - Kolibaba, Larysa; Romaniuk, Svitlana (Papers in Linguistics, 2022)
The aim of this article is to present various grammatical forms of expressions to persons in texts being part of contemporary political discourse, and to analyse them in the light of current morphological standard included in new edition of „Ukrainskyi pravopys” of 2019, as well as to compare them with morphological standards specified in previous edition of „Ukrainskyi pravopys” of 1993. Normative grammatical forms of expressions to persons are of particular interest. Changes in use of the vocative included in new „Ukrainskyi pravopys” are characterized, and also their application in contemporary